The Evolution of Afghanistan's Borders Throughout History and Its Geopolitical Impacts - Fayaz Gul Mazloum Yar; Sayed Habibullah Sadaat (Green Publisher Indonesia, 2025)
This research explores the historical evolution of Afghanistan's borders and their geopolitical impacts. The main goal of the study is to analyze how changes in Afghanistan's borders have influenced its security, economy, international relations, and domestic politics, as well as its role in regional and global power dynamics. The research uses a systematic review of historical sources, geopolitical analyses, and both qualitative and quantitative data. The sources include historical treaties, diplomatic documents, reports from international organizations, and academic studies published. The findings reveal that Afghanistan's borders have undergone significant changes throughout history, largely influenced by colonial powers and regional rivalries. These border changes have had profound effects on Afghanistan's national and regional security, contributing to issues such as drug trafficking, terrorism, and illegal migration. Additionally, Afghanistan's economy has been heavily impacted by unstable borders and political tensions with neighboring countries. The creation of artificial borders, such as the Durand Line, has also led to ethnic and identity challenges within the country. Due to its strategic location, Afghanistan plays a crucial role in regional and global power dynamics. The country's borders have not only shaped its internal structure but have also had significant implications for international relations and regional security. To stabilize its borders and enhance overall stability, Afghanistan must engage in active diplomacy, foster regional economic cooperation, and implement effective border management strategies. These measures can help strengthen Afghanistan's position in regional and global power dynamics, contributing to long-term peace and development.